Identification And Characterization Of Endophytic Fungi From Spines Of Rattan (Calamus castaneus) - Azuddin, Nurul Farizah (2020)
Endophytic fungi are fungi residing within plant tissues without causing any negative effects to the host. The present study was conducted to determine whether spines of Calamus castaneus harbour endophytic fungi. Calamus castaneus (rotan cucor) was chosen as the palm is among common and ecologically important plant in Malaysian forests. Spines of rattan are regarded as physical defensive structure against herbivores and reported to contained human pathogens. Morphological characteristics were used to tentatively identify the endophytic fungal isolates to genus or species levels. Depending on the genus, different sets of gene were applied for molecular identification and phylogenetic analysis.